2017
DOI: 10.1590/0104-070720170003140016
|View full text |Cite
|
Sign up to set email alerts
|

Competências Do Enfermeiro Na Prevenção De Quedas Em Crianças À Luz Do Consenso De Galway

Abstract: Objective: to analyze nurses' abilities regarding the prevention of falls in hospitalized children in light of the Galway Consensus.Method: a cross-sectional study was conducted with 40 nurses who worked in the open hospitalization units of a pediatric hospital. Data collection was performed through the application of a questionnaire with validated content. The actions performed by the nurses, according to the fall prevention protocol, were related to the eight domains of the Galway health promotion competency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 17 publications
1
16
0
4
Order By: Relevance
“…In Figure 1, the selection process of the articles with a PRISMA flow chart is presented, with the seven included in the final sample (two articles from EBSCO [CINAHL and MEDLINE] (20)(21) , four articles from PubMed (22)(23)(24)(25) and one article from SciELO (26) ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In Figure 1, the selection process of the articles with a PRISMA flow chart is presented, with the seven included in the final sample (two articles from EBSCO [CINAHL and MEDLINE] (20)(21) , four articles from PubMed (22)(23)(24)(25) and one article from SciELO (26) ).…”
Section: Resultsmentioning
confidence: 99%
“…Competencies of the Nurse in the Prevention of Falls in Children in the Light of the Galway Consensus (2017) (26) -Most used fall prevention nursing interventions were: inform whether the child can walk or not (97.5%), educate the child/caregiver about the risk of falling (92.5%), assess the risk of falls at the moment after admission (92.5%), arrange for transportation on a stretcher or wheelchair (95%), keep one of the crates lifted from the cradle during the child's clothes/diaper change (92.5%).…”
Section: Title Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of nurses' skills in preventing falls in hospitalized children, in the light of the Galway Consensus, identified that among these, the Leadership domain was present in all actions. It also found that continuing education for the implementation of a practice based on health promotion is considerable (21) .…”
Section: Discussionmentioning
confidence: 99%